Assessing determinants of pre-exposure prophylaxis (PrEP) adherence among a sample of rural Midwestern men who have sex with men (MSM). Issue 12 (1st December 2020) - Owens, Christopher; Hubach, Randolph D.; Lester, Jessica Nina; Williams, Deana; Voorheis, Eva; Reece, Michael; Dodge, Brian
ABSTRACT: Pre-exposure prophylaxis (PrEP) efficacy in preventing HIV among gay, bisexual, and other men who have sex with men (MSM) is dependent upon adherence. Little is known about the PrEP adherence experiences among MSM who live in rural areas of the US. This qualitative study was informed by a modified version of Straussian Grounded Theory. Thirty-four 34 rural Midwestern MSM participated in telephone interviews that assessed their PrEP adherence factors. Overall, participants adhered to the PrEP regimen, ranging from missing none to a couple of doses per month. Participants had high self-efficacy (competence) and self-reliance (autonomy) in taking PrEP daily. Participants incorporated PrEP into their already existing routines. Participants were motivated to adhere to prevent HIV acquisition and be financially responsible. All participants mentioned their PrEP provider discussed the importance of adherence with PrEP's effectiveness, but future patient-provider PrEP adherence communication varied among participants. Future PrEP adherence interventions should address counseling strategies that leverage these constructs to support pill taking. Future research should explore patient-provider conversations surrounding PrEP adherence to inform provider- and patient-level interventions.